'Home Rule is Rome Rule': exploring anti-Home Rule postcards in Edwardian Ireland. Issue 4 (7th August 2020) - O'Hagan, Lauren
Abstract : In 1912, the British government introduced a Home Rule Bill to Parliament, proposing that Ireland be granted the right to self-govern. This Bill provoked widespread outrage in the Ulster province of Ireland, where most people were Protestant and felt strongly in support of the Union. To express their opposition to Home Rule, Ulster Unionists produced propaganda postcards to convince fellow Irish citizens, the British government and the British public of their cause. This paper analyses six examples of anti-Home Rule picture postcards produced by Ulster Unionists in Belfast between 1912 and 1914. It groups them into six themes – British patriotism; Ulster loyalism; Protestantism; Violence; Mockery of Irish Nationalists; and Comic relief – and uses multimodal critical discourse analysis to explore the ideologies and messages promoted by their iconography. It concludes that, while these postcards aimed to show Ulster as united in its common objective of stopping the Home Rule Bill, their broad range of rhetoric and semiotic resources, in fact, reflects the lack of political consensus across the province and forecasts some of the troubles to come. Nonetheless, it asserts that, despite their contradictions, their hugely emotive power, coupled with other propaganda resources, was successful at drawing attention to Ulster's cause and putting the province into the spotlight.